Improvement of l-ornithine production by attenuation of argF in engineered Corynebacterium glutamicum S9114 - Zhang, Bin (AMB Express, 2018)
l-Ornithine, a non-essential amino acid, has enormous industrial applications in food, pharmaceutical, and chemical industries. Currently, l-ornithine production is focused on microorganism fermentation using Escherichia coli or Corynebacterium glutamicum. In C. glutamicum, development of high l-ornithine producing C. glutamicum was achieved by deletion of argF, but was accompanied by growth deficiency and arginine auxotrophy. l-Arginine has been routinely added to solve this problem; however, this increases production cost and causes feedback inhibition of N-acetyl-l-glutamate kinase activity. To avoid the drawbacks of growth disturbance due to disruption of ArgF, strategies were adopted to attenuate its expression. Firstly, ribosome binding site substitution and start codon replacement were introduced to construct recombinant C. glutamiucm strains, which resulted in an undesirable l-ornithine production titer. Then, we inserted a terminator (rrnB) between argD and argF, which significantly improved l-ornithine production and relieved growth disturbance. Transcription analysis confirmed that a terminator can be used to downregulate expression of argF and simultaneously improve the transcriptional level of genes in front of argF. Using disparate terminators to attenuate expression of argF, an optimal strain (CO-9) with a T4 terminator produced 6.1 g/L of l-ornithine, which is 42.8% higher than that produced by strain CO-1, and is 11.2-fold higher than that of the parent CO strain. Insertion of terminators with gradient termination intensity can be a stable and powerful method to exert precise control of the expression level of argF in the development of l-ornithine producing strains, with potential applications in metabolic engineering and synthetic biology. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13568-018-0557-8) contains supplementary material, which is available to authorized users.